The Role of Women in Creating A More Just World Civilization - Susilawati, Susilawati; XL, Lemhannas (PT FORMOSA CENDEKIA GLOBAL, 2024)
Women have an important role in realizing a just world civilization. Although there are physiological differences between women and men that influence their roles in society, the modern era opens up wider opportunities for women to develop. With increased literacy in the digital era, women are increasingly realizing their career potential outside of household duties. Women have brought unique perspectives in various fields through their roles, ranging from agents of peace, educators of the next generation, leaders and decision makers, economic drivers, and guardians of the balance of nature. However, until now they still face challenges such as discrimination and violence. To overcome this, concrete efforts are needed, especially in supporting gender equality in society by strengthening women's leadership.